Congenital Hydrocephalus and Associated Risk Factors: An Institution-Based Case–Control Study, Dessie Town, North East Ethiopia - Abebe MS; Seyoum G; Emamu B; Teshome D (Dove Medical Press, 2022)
Melese Shenkut Abebe,1 Girma Seyoum,2 Bahru Emamu,3 Demissie Teshome4 1Department of Anatomy, School of Medicine, College of Health Science, Wollo University, Dessie, Ethiopia; 2Department of Anatomy, School of Medicine, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 3Department of Radiology, School of Medicine, College of Medicine and Health Science, Wollo University, Dessie, Ethiopia; 4Department of Radiography, Dessie Health Science College, Dessie, EthiopiaCorrespondence: Melese Shenkut Abebe, Department of Anatomy, School of Medicine, College of Health Science, Wollo University, Dessie, Ethiopia, Email melese19@yahoo.comIntroduction: Congenital hydrocephalus is one of the commonest congenital anomalies of the central nervous system. It is characterized by extensive accumulation of cerebrospinal fluid within the ventricles of the brain due to an imbalance between synthesis and absorption of cerebrospinal fluid. This study was planned to investigate the incidence and associated risk factors of congenital hydrocephalus.Methods: Unmatched case-control study was conducted in 34 (cases) and 104 (controls) pregnant women. Maternal data were collected from a structured questionnaire, and fetal-related data were recorded from obstetric ultrasound. Epi-info 7 and SPSS version 24 were used for data entry and analysis, respectively. The association between congenital hydrocephalus and risk factors was evaluated using binary logistic regression.Results: The incidence of congenital hydrocephalus was 2.67 per 1000 pregnancies. The result of multivariate logistic regression indicated that alcohol use and iron with folic acid supplementation during pregnancy were significantly associated with the development of congenital hydrocephalus (OR: 7.64, 95% CI: 1.97- 29.66 and p-value: 0.003 and OR: 0.186, 95% CI: 0.07- 0.49 and p-value: 0.001, respectively). Maternal exposure to typhus and typhoid and use of antibiotics during early pregnancy were also significantly associated with congenital hydrocephalus. Moreover, significant association was also observed between the simultaneous development of spina bifida and congenital hydrocephalus (p-value 0.03).Conclusion: In conclusion, alcohol consumption, unprescribed use of antibiotics and infection during pregnancy as well as absence of folic acid supplementation may predispose to congenital hydrocephalus.Keywords: case control, congenital anomaly, hydrocephalus, nervous system